Farelo da semente de maracujá na alimentação de suínos na fase inicial - Fachinello, Marcelise Regina (2014)
Two experiments were conducted to determine the nutritional value of the passion fruit seed meal (PFSM) and evaluate the performance, blood parameter, quantitative parameters of the carcass and economic viability of swine in the initial phase, fed diets containing different PFSM levels inclusion. Experiment I: A digestibility trial was conducted to determine the nutritional value of the PFSM. 25 barrows were used, with initial weight of 19.08 ± 2.81 kg, distributed individually in metabolism cages, in a completely randomized block design, consisting of five treatments and five replicates. The treatments consisted of a reference diet and four levels of PFSM replacement (4, 8, 12 and 16%) by the reference diet. The digestible nutrients, digestible and metabolizable energy were determined through adjustments of linear equations. Experiment II: An experiment was conducted to evaluate the performance of swine in the initial phase fed PFSM. 60 pigs (30 females and 30 castrated males) were used, with initial body weight of 15.45 ± 0.87 kg, distributed in a randomized block design, with five treatments, six replicates and two animals per experimental unit. The treatments consisted of increasing levels of PFSM inclusion (0, 4, 8, 12 and 16%). Consequently, the digestible energy (DE) and metabolizable energy (ME) equations: Ŷ= 3.974x + 15.789 (r²= 0,97) and Ŷ= 3.583x + 1.55 (r²= 0.95) were adjusted respectively, and thus, the DE was estimated at 3.974 kcal / kg and the ME at 3.583 kcal/kg, and the ME:DE ratio was 0.90. The equations for digestible protein (DP)= 8.00x + 0.115 (r²=0.90), digestible ether extract (DEE)= 17.32x - 0.604 (r²= 0.99), digestible neutral detergent fiber (NDF)= 25.04x - 0.235 (r²= 0.91) and digestible acid detergent fiber (DADF)= 19.60x + 0.036 (r²= 0.80) were adjusted. There was no effect (P> 0.05) of the PFSM inclusion on the daily weight gain variables, feed take, feed conversion, back fat thickness, loin depth, and the blood parameters evaluated. PFSM was not economically attractive for inclusion levels evaluated, according to the prices prevailing in the trial period. It is concluded that the values of digestible and metabolizable energy of passion fruit seed meal, for swine in the initial phase, were 3.974 kcal/kg and 3.583 kcal/kg, respectively, and for dry matter, organic matter, protein, ether extract, neutral detergent fiber and acid detergent fiber digestible were 62.39, 59.62, 8.00, 17.32, 25.04 and 19.60%, respectively. The PFSM can be added up to 16% in diets for swine in the initial phase, without influencing performance, quantitative carcass characteristics, blood parameters and the economical aspect will depend on its price and the other ingredients to be used in the ration.